ANALYZING CUSTOMER PERCEPTION ON PRODUCT ATTRIBUTES OF SMARTPHONE (OPPO, XIAOMI, ZENFONE) IN MANADO - Sjamsoedin, Junistia Priscilla; Saerang, David Paul Elia (Universitas Sam Ratulangi, 2014)
Smartphone provides a one stop solution for mobile calls, email sending, and internet access, Smartphone is compact in size and often only slightly bigger than standard mobile phone. Recently the Smartphone sales increased for the brand at an affordable price as Oppo, Xiaomi, and Zenfone. That is why those Smartphone are bought by many people in Manado. This research is designed to provide information about marketing implementation and get a better knowledge regarding the role of product attributes of Oppo, Xiaomi and Zenfone. The method used in this research is quantitative research method using correspondent analysis which will provide an emphasis on numerical data (number) processed with statistical methods. The data from this research were gathered by using questionnaire, which the sample is the representative customer with simple random sampling approach. There are several points that can be found to be the main point is that each Smartphone has their own benefit and luxury offers by the companies. The result of this study confirms that according to customer perception, Zenfone has the very good function, ease of use, design, eco-friendliness and satisfaction compare with the two product Smartphone, in this case Xiaomi and Oppo. In the terms of reliability and durability, Oppo is more superior. Xiaomi’s product attributes are less attractive compare to both of its competitors according to customer perception. Keywords: customer perception, product attributes, smartphone